The Virus Infection and Biliary Atresia - Feng, Jiexiong; Huang, Lei (Current Pediatric Reviews, 2008)
Biliary Atresia (BA) is one of the most common cause of neonatal cholestasis with unclear pathogenesis currently. Virological investigations had proved that BA might be closely connected with the pathogen infections especially viral infection. In this article, we have summarized the recent advancements in viral etiology and epidemiology of BA, presented the possible etiological factors such as cytomegalovirus (CMV), reovirus, rotavirus, human papilloma virus (HPV) and illuminated the unknowns of this disease and further research directions in the future. Epidemiologic studies had demonstrated a close relationship between BA and some kinds of explosive pathogen infections for its high seasonal and regional characters, which might present with different patterns in different countries. Virological researches had shown BA infants had a high rate of CMV infection detected both in blood and tissues samples. What's more, pregnant mice and newborn mice which were infected by reovirus and rotavirus could be developed into BA model. However, relationship between other viruses such as HPV and HHV-6 and BA needs further investigation. With the development of laboratory techniques and deep research in different areas, consummate and precise viral etiology of BA will be established to guide our clinical and research work in the future.
Keywords: epidemiology